Implementasi Metode Sorogan Dalam Meningkatkan Pemahaman Kitab Fathul Qorib Pada Santri Pondok Pesantren Ngalah Pasuruan - Oktariani Dwi Ningtiyas (4, 2025)
Education in Islamic boarding schools currently faces challenges in improving reading skills, especially at the elementary level. Ngalah Islamic Boarding School is a modern Islamic boarding school that still uses traditional learning methods. One such method is the sorogan method, which utilizes the Fathul Qorib book. The sorogan method involves students individually approaching a Kyai (Islamic teacher), who will read several lines of an Arabic text and translate them into a specific language. The students then repeat and translate, or